CSR, Corporate Governance, Firm Size and Earnings Management: Empirical Evidence from Indonesian Infrastructure Firms on the IDX - Sultan Achmad Daffa; Roy Budiharjo (LP2M IAIN Palopo, 2026)
Corporate social responsibility (CSR), institutional ownership (IOW), audit committees, and company size (F size) are the variables that this study intends to examine in relation to earnings management. Companies listed on the IDX in the infrastructure industry from 2021–2025 are the main emphasis. We selected 20 out of 70 listed infrastructure businesses using a purposive sample technique and a quantitative research strategy based on secondary panel data for this study. Panel data regression analysis was used for hypothesis testing, and discretionary accruals were created from the Modified Jones Model to quantify earnings management. Chow, Hausman, and Lagrange Multiplier tests determined that the REM was the best fit. An Adjusted R-squared score of 19.20% shows that earnings management is significantly affected by all four independent factors. Earnings management and CSR disclosure show a negative correlation, although audit committee, firm size, and institutional ownership by themselves do not. Although firm size, audit committee meeting frequency, and concentration of institutional ownership are not sufficient factors to prevent managerial opportunism in the infrastructure industry, these results suggest that CSR disclosure is a useful tool for keeping earnings management practices in check. Investors, regulators, and corporate governance frameworks in Indonesia's infrastructure industry can benefit from this research, which also advances agency theory.